Theory of cryptography 8th Theory of cryptography conference, TCC 2011, Providence, RI, USA, March 28-30, 2011. Proceedings - Ishai, Yuval (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed proceedings of the 8th Theory of Cryptography Conference, TCC 2011, held in Providence, Rhode Island, USA, in March 2011. The 35 revised full papers are presented together with 2 invited talks and were carefully reviewed and selected from 108 submissions. The papers are organized in topical sections on hardness amplification, leakage resilience, tamper resilience, encryption, composable security, secure computation, privacy, coin tossing and pseudorandomness, black-box constructions and separations, and black box separations.